Effects of different arm actions on performance in long distance running - Mwangi, F.; Wanderi, P.; Wamukoya, E, (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
The study investigated how different arm actions affected cardio-respiratory parameters and stride patterns during the steady phase of long distance running. Mean values of working heart rate (WHR), recovery heart rate (RHR), percentage of maximum oxygen consumption (%VO2 max), ventilation rate (VR), and rating of perceived exertion (RPE) were used to estimate physiological demands and the energy cost of running with different arm actions, thus helped to evaluate and compare their effects on running economy (RE). Ten elite Kenyan endurance athletes of both sexes (Training Age = 9.750 ± 5.560; Mean ± SD) were selected through purposive sampling procedures and tested in ten submaximal treadmill trial runs, each trial performed with different arm action for 15 minutes at a speed corresponding to individual`s 80% running effort. Their working and recovery heart rates were monitored (using Polar heart rate monitor) during each trial, as well as the rating of perceived exertion (using Borg Scale of perceived exertion), ventilation rate (VR) and stride rate (SR). The values were recorded after every five minutes. The Cooper test was used to estimate the subjects` VO2 max. Regression equations were used to estimate percentage of maximum oxygen consumption (%VO2 max) and kilocalories expended (Kcl) from working heart rate values. ANOVA with Repeated Measures was used to analyze the data, using the SPSS software. Significant difference was observed in WHR, %VO2 max, Kcl, RPE, and SR at p < .05. Intraclass Correlation Coefficient (R) analysis of individuals` trial-to-trial test values showed high reliability for all the variables measurements and procedures (WHR; .98, RHR; .91, RPE; .83, VR; .99, SR; .90, %VO2 max; .98, Kcl; .97). Medium effect size was observed; Omega Squared ( 2) = .20, indicating practical significance of the results. The study concluded that arm action consisting of about ±20 degrees oscillation of the hands around 90 degrees angle at the elbow is more economical than running with the arm action recommended by many authors (with arms held at 90 degrees angle at the elbows), and that different arm actions have different effects on the various components of running mechanics. The study recommended that arm action consisting of about 30 degrees elbow angle range of oscillation -arm action involving oscillation of elbow angles from 70 degrees (on fore swing) to 100 degrees (on backswing), be adopted by distant runners for optimum performance.